2021
DOI: 10.7554/elife.67495
|View full text |Cite
|
Sign up to set email alerts
|

Two different cell-cycle processes determine the timing of cell division in Escherichia coli

Abstract: Cells must control the cell cycle to ensure that key processes are brought to completion. In Escherichia coli, it is controversial whether cell division is tied to chromosome replication or to a replication-independent inter-division process. A recent model suggests instead that both processes may limit cell division with comparable odds in single cells. Here, we tested this possibility experimentally by monitoring single-cell division and replication over multiple generations at slow growth. We then perturbed… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
34
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(46 citation statements)
references
References 57 publications
11
34
1
Order By: Relevance
“…However, DNA replication re-initiation events were identified by examining the relative position of the (brightest) SeqA-mCherry focus, which moved from midcell to a quarter cell position upon re-initiation (Figures 3C and S1C). In contrast to how it has occasionally been interpreted 68,79 , this re-localization did not appear to be preceded by a termination event, as cells without ongoing DNA replication could not be detected (based on the relative area of the SeqA-mCherry signal; Figure S1C) in these nutrient-rich conditions. The presence of overlapping rounds of DNA replication, where a new round initiates before the previous one has terminated, is also in line with what is known about chromosome replication in E. coli in richer growth conditions (supporting growth rates > ~1 h -4 ) 8 .…”
Section: Star Methodscontrasting
confidence: 62%
See 1 more Smart Citation
“…However, DNA replication re-initiation events were identified by examining the relative position of the (brightest) SeqA-mCherry focus, which moved from midcell to a quarter cell position upon re-initiation (Figures 3C and S1C). In contrast to how it has occasionally been interpreted 68,79 , this re-localization did not appear to be preceded by a termination event, as cells without ongoing DNA replication could not be detected (based on the relative area of the SeqA-mCherry signal; Figure S1C) in these nutrient-rich conditions. The presence of overlapping rounds of DNA replication, where a new round initiates before the previous one has terminated, is also in line with what is known about chromosome replication in E. coli in richer growth conditions (supporting growth rates > ~1 h -4 ) 8 .…”
Section: Star Methodscontrasting
confidence: 62%
“…Throughout our analysis, we did not find any direct connection between DNA replication and division events across strains and media, supporting the idea that the DNA replication and cell division cycles operate largely independently. This is important as a wealth of models have been proposed to explain if and how cell division is controlled by DNA replication 13,21,39,44,53,66,67,[77][78][79][80] .…”
Section: Points Of Control and Integrationmentioning
confidence: 99%
“…The regulation proposed in Figure 6 is similar to the concurrent processes model ( Micali et al, 2018a , 2018b ; Colin et al, 2021 ), with some differences. First, the concurrent processes model does not consider the initiation of the constriction as a cell-cycle checkpoint.…”
Section: Discussionmentioning
confidence: 99%
“…However, several other works have concluded that the replication and division cycles in E. coli are independent of each other ( Bernander and Nordstrom, 1990 ; Campos et al, 2014 ; Taheri-Araghi et al, 2015 ; Si et al, 2019 ; Harris and Theriot, 2016 ). As the middle ground of these opposing views, it has been recently proposed that division is controlled concurrently by replication and growth-related processes; whichever of these processes completes the latest will trigger cell division ( Micali et al, 2018a , 2018b ; Colin et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent experiments support the hypothesis that cell division is regulated by both replication and replication‐independent events. [ 51 ] Therefore, we speculate that the hydrogel matrix may be stopping cell division by either suppressing DNA replication, restricting the increase in cell size, or both. To provide a definitive answer, subsequent work may combine Cryo‐EM, high‐resolution microscopy, and proteomic analysis at different stages of the lifespan of the Cyborg Cells to reveal localized protein‐hydrogel interactions.…”
Section: Discussionmentioning
confidence: 99%